Need analysis of learning local content of bahasa Toraja in elementary school students - Resnita Dewi; Anastasia Baan; Roberto Salu Situru; Roni La’biran; Engel Gelong (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
The native knowledge of Indonesia, including the Toraja, is slowly fading as other cultures take over. As a result, promoting learning grounded in local knowledge through Bahasa Toraja's local content is essential. Examining the prerequisites for instructors and students to understand local content in primary schools is the goal of this study. In line with that, this research aims to define the teaching standards and learn Bahasa Toraja's regional components. This is necessary to fulfill its purpose as a venue for introducing and maintaining local wisdom and to make the previously unappealing and in-demand process of learning local material engaging. This research is of the mixed method type. This mixed-method research uses a sequential explanatory approach. This research was conducted for grade IV elementary school students at SD N 1 Kepe' for the 2021/2022 school year, North Toraja. Miles and Huberman's model was used to analyze the data, consisting of three key steps: data reduction, data presentation, and findings. The study's findings indicate that to increase the quality of the local content of the Toraja language to maintain Toraja culture and local knowledge, students' and instructors' demands in learning the local content of the Toraja language must be taken into account.